Occurrence of the JAK2 V617F mutation in patients with peripheral arterial disease. Issue 1 (20th November 2014) - Muendlein, Axel; Kinz, Elena; Gasser, Klaus; Leiherer, Andreas; Rein, Philipp; Saely, Christoph H.; Grallert, Harald; Peters, Annette; Fraunberger, Peter; Drexel, Heinz; Lang, Alois H.
<x xml:space="preserve">Abstract</x> The acquired JAK2 V617F mutation is common in patients with myeloproliferative neoplasms. We previously showed that JAK2 V617F is also found in coronary patients, most of them affected by coronary atherosclerosis. Peripheral arterial disease (PAD) is another important manifestation of atherosclerosis. However, prevalence of the JAK2 V617F mutation and its effect on clinical or hematologic characteristics is unknown in PAD patients. In the present study we determined the prevalence of JAK2 V617F in a cohort of 287 patients with sonographically proven PAD and compared mutation frequency with mutational status of 997 healthy people from the KORA F4 study. JAK2 V617F screening and quantification of allele burden in both cohorts was performed with same allele‐specific quantitative real‐time PCR method. From a total of 287 PAD patients, 9 individuals were tested positive for the JAK2 V617F mutation. One patient showed elevated hemoglobin values, indicating polycythemia vera. Observed JAK2 V617F frequency (3.1%) in PAD patients showed a 5‐fold, highly significant increase compared with healthy people (P < 0.001). Furthermore, occurrence of the mutation in PAD patients was significantly decreased in patients using aspirin (P = 0.003). We conclude that the prevalence of JAK2 V617F mutation is significantly increased in PAD patients compared to the general population. Future studies are warranted to confirm our observations and to define the underlying mechanisms behind our findings. Am. J. Hematol. 90:E17–E21, 2015. © 2014 Wiley Periodicals, Inc.